Legal Measures to Prevent and Overcome the Occurrence of Drug Crime - Indriyanti Agustina Rahjm (Universitas Negeri Gorontalo, 2023)
The purpose of this research is to find out and analyze the legal efforts that have been made in preventing and overcoming drug crimes in the city of Gorontalo.This research uses a type of empirical legal research that uses facts in the field as the main data in compiling the research. The type of data used is primary data consisting of interviews with respondents, observation and documentation; and secondary data consisting of books, scientific articles, and other data sources that are considered related to the issue being discussed. The results of the study show that first, the factors that cause drug crime in Gorontalo City are economic factors, psychological factors, and environmental factors.Second,the legal remedy carried out by the investigator at the Gorontalo City Police for drug crimes is to take action as determined.